The T alpha 1 alpha-tubulin promoter specifies gene expression as a function of neuronal growth and regeneration in transgenic mice - Gloster, A (J Neurosci, 1994)
We have previously demonstrated that one member of the alpha-tubulin multigene family, termed T alpha 1 in rats, is regulated as a function of neuronal growth and regeneration. To elucidate the molecular mechanisms responsible for coupling gene expression to morphological differentiation, we have isolated the T alpha 1 gene, have fused 1.1 kb of the 5′ flanking region to a nuclear lacZ reporter gene, and have generated transgenic mice. Analysis of these transgenic mice demonstrated that marker gene expression was specific to the CNS and PNS, with expression in vivo at embryonic day 13.5 being similar to expression of the endogenous gene. Moreover, the induction of transgene expression was correlated temporally with neuronal commitment in developing neural crest-derived peripheral neurons and in the developing retina. Immunocytochemical analysis of mixed primary embryonic brain cultures confirmed that transgene expression was specific to neurons, with the majority of neurons, but not astrocytes or oligodendrocytes, expressing beta-galactosidase. Transgene expression in vivo was maintained in developing neurons until early in postnatal life, subsequent to which its expression decreased coincident with neuronal maturation. The transgene was then reinduced in regenerating facial motoneurons following unilateral axotomy of the facial nerve. Thus, 1.1 kb of 5′ flanking sequence from the T alpha 1 gene contains the sequence elements responsible for specifying gene expression to embryonic neurons and for subsequently regulating gene expression in both developing and mature neurons as a function of morphological growth.